Propetips: a formative experience of good practices in scientific production at a public university - Hayashi, Maria Cristina Piumbato Innocentini; Guimarães, José Augusto Chaves [UNESP] (University Library System, University of Pittsburgh, 2024)
Objective: This study aims to analyze the contributions of the Propetips series – a collection of texts produced by the Vice-Rectorate of Research at UNESP to the promotion of good practices in scientific production and dissemination among members of its academic community. Method. This is an exploratory-descriptive research of a theoretical and applied nature, with a qualitative and quantitative approach. The thematic categories for the analysis of the Propetips were developed ex-ante based on an extensive review of the scientific literature on scholarly literacy, a comprehensive concept that encompasses the skills and knowledge necessary for effective participation in academic discourse. In the qualitative analysis, the content of the Propetips was explored to understand how each one contributes to the identified thematic categories, discussing the relevance and practical implications of the guidelines provided. In the quantitative analysis, the frequency of thematic categories and the presence of thematic overlaps were used as indicators to quantify the scope and focus of the Propetips. Results. Ten thematic categories of current Propetips were identified (collaboration and academic networks, academic career development, publication strategies, research funding and support, research data management, integrity and ethics in science, scientific metrics, scientific recognition, review by peers, scientific visibility). It was found that the categories “publication strategies” and “ethics and integrity” were the most frequent, representing, together, 51.2% (n=21) of the total. The other categories (n=6) covered 34.1% (n=14) of the total, and the remaining six were double categorized, as they reflected the complexity and interconnection of the challenges faced in the contemporary academic environment. For future expansion of Propetips, 12 themes were identified (open access and scientific repositories, open and collaborative science, scientific communication for non-specialized audiences, diversity, equity, inclusion and accessibility in research, continuing education, multimedia digital tools, scientific communication, innovation and academic entrepreneurship, artificial intelligence and research, editorial process, retraction of scientific articles, sustainability and research, technology and innovation in research). Feedback from the academic community revealed the interest and importance of Propetips in the daily lives of teachers and researchers. Conclusions. The study highlighted the relevance and impact of Propetips on the academic community at Unesp, highlighting its contribution to promoting scientific integrity and improving good research and publication practices. It also highlighted the importance of initiatives of this nature for the academic and scientific literacy of postgraduate students and young teachers in their academic careers.
Propetips: una experiencia formativa de boas prácticas en producción científica en la universidad pública
Propetips: uma experiência formativa de boas práticas em produção científica na universidade pública
Keywords: Good practice in scientific publications; Scholarly communication; Unesp-Propetips